Paranoia with a purpose: conspiracy theory and political coalitions in Kyrgyzstan. Issue 5 (2nd September 2016) - Radnitz, Scott
Abstract: This article considers the political uses of conspiracy theories (CTs). It is widely accepted that post-Soviet citizens are prone to believe CTs, but there has been little research about the conditions under which politicians endorse conspiracy narratives and why those narratives sometimes become hegemonic. I argue that in times of high uncertainty, CTs have properties that are useful in providing political elites with a focal point for coordination in the absence of other bases for coalition formation. I demonstrate this logic by analyzing the politics surrounding the construction and spread of a conspiracy narrative following violence in Kyrgyzstan in 2010. Politicians with different interpretations of the event coalesced around a contrived conspiratorial narrative, and used it to paper over differences as they formed a ruling coalition. This argument has implications for how to understand the appearance and durability of conspiracy claims in states where political formations are fluid.